Ultrasonic volume assessment-guided successful rescue of cardiac arrest caused by intraoperative severe anaphylactic shock: a case report - Yin-guang Yao; Zhi-lan Dou; Fang Zheng; kai-lai Zhu; Jian-Wei Zhou; Jian Zhou; Chuan-Guang Wang (BMC Anesthesiology)
Abstract Background Perioperative anaphylaxis (POA) is a potentially life-threatening event. The incidence of POA is on the rise, but few case reports are available on cardiac arrest caused by post-anesthesia anaphylactic shock especially those successfully rescued under the guidance of ultrasonic volume assessment. Case presentation We herein report a case of cardiac arrest caused by intraoperative anaphylactic shock. A patient was admitted to the hospital due to left lumbar pain for two days and was diagnosed with left renal and ureteral calculi accompanied by hydronephrosis and infection. She was scheduled to undergo transurethral flexible ureteroscopic lithotripsy for bilateral renal and ureteral calculi under general anesthesia. Refractory hypotension occurred intraoperatively, so vasoactive drugs were applied, but the effect was unsatisfactory and cardiac arrest occurred later. At that time, the patient did not develop common allergic symptoms such as rash. After cardiopulmonary resuscitation (CPR), the patient’s heart rate recovered, but she still presented with persistent hypotension. After the anesthesiologist carried out ultrasonic volume assessment-guided fluid resuscitation, the patient experienced systemic rash, in which case severe anaphylactic shock was confirmed. After epinephrine and antianaphylactic treatment were given, the patient’s vital signs tended to become stable, and the operation was successfully completed. Conclusion With the assistance of the medical team, we successfully rescued a patient with cardiac arrest caused by intraoperative severe anaphylactic shock under the guidance of ultrasonic volume assessment. The operation was successfully completed, and the patient was discharged two days postoperatively and had a good prognosis.